Chronic traumatic encephalopathy – current state of knowledge - Bryliński, Łukasz; Drożak, Paulina; Drożak, Martyna; Augustowska, Katarzyna; Duda, Piotr; Bura, Agata; Rudnicka-Drożak, Ewa (Journal of Education, Health and Sport, 2021)
Introduction and purpose. Chronic traumatic encephalopathy (CTE) is a tauopathy caused by repetitive, mild head injuries. It is characterized by perivascular accumulation of hyperphosphorylated tau protein in the neurons and astrocytes. CTE leads to changes in central nervous system, both on microscopic and macroscopic level. The aim of the study was to present the current knowledge on chronic traumatic encephalopathy among athletes, its predisposing factors, symptoms and consequences, as well as diagnostic methods and treatment. Description. CTE occurs among contact sport players, such as American football, ice hockey, soccer, baseball, box and MMA (mixed martial arts), as well as among soldiers and victims of domestic violence. Repetitive head injuries and long career duration increase the risk of CTE. Symptoms of chronic traumatic encephalopathy include a commonly occurring triad: cognitive disturbances, behavioral problems and mood disturbances. Other symptoms include memory loss, parkinsonism, headaches, speech and walking problems. Currently, the only diagnostic method of CTE is a posthumous detection of neuropathological markers. Methods such as detection of exosomal tau protein in plasma and imaging techniques give hope to diagnose CTE in alive patients. Treatment methods of CTE, such as LIPUS (low intensity pulsed ultrasound) therapy are currently being developed. Conclusions. Chronic traumatic encephalopathy among athletes is a serious problem that affects multiple people due to the popularity of contact sports. Thus, an emphasis should be put on prevention, raising awareness and appropriate protection of athletes through changes in regulations and improvement of protective equipment.